Use of an Active Thinking Approach Using Interactive Media to Improve Class III Writing Skills - Sartika, Diana; Kuntarto, Eko; Pamela, Issaura Sherly (FKIP - Universitas Riau, 2024)
This research was motivated by the low writing skills of class III students at SDN 13/I Muara Bulian. This research is Classroom Action Research (PTK) which aims to describe the use of the MIKiR active approach using interactive media to improve writing skills in class III. This research was conducted at SDN 13/I Muara Bulian. Research data was obtained using observation, interviews, tests and documentation techniques. The types of data in this research are qualitative and quantitative data. The research results show that using the MIKiR active approach in the learning process using interactive media can improve writing skills in class III. This can be seen from the results of observations in cycle I, meeting I, the average percentage of 41.03% was still in the quite good criteria and this percentage increased because at meeting II the average percentage was 46.73% even though it was still in the quite good category. In cycle II there was a significant increase where from the average percentage of students' scores in cycle II, meeting I, the average percentage was 63.58%, which was still within the good criteria and this percentage increased because at meeting II the average percentage was 75.54%, which was included into the very good category. In this case it is concluded that the use of the MIKiR active approach using interactive media can improve writing skills in class III at SDN 13/I Muara Bulian.